Carbon–silica composite nanofiber membrane for high flux separation of water-in-oil emulsion – Performance study and fouling mechanism - Tai, Ming Hang (2015)
A flexible, hydrophobic and oleophilic carbon nanofiber membrane was prepared from electrospinning for cross-flow filtration of water-in-oil emulsion under various operating conditions. Experimental results show that the membrane has a high throughput of clean oil at low pressure. Furthermore, the membrane performance in terms of permeate flux was governed by the operating pressure and cross-flow velocity. The membrane has a water breakthrough pressure of 0.206 bar under constant cross-flow velocity. The investigation of membrane fouling mechanisms using pore blocking models and resistance model reveals that the membrane experiences either of external or internal fouling or a combination of both under different operating conditions. Using the contour plot analysis, it was suggested that the optimum operating conditions for the membrane to perform efficiently shall be at high cross-flow velocity and at low pressure (between 0.07 and 0.206 bar). Keywords: Electrospinning; Carbon nanofiber; Superoleophilicity; Membrane; Oil–water separation